Assistance for Children with Special Needs in Inclusive Schools Through Guidance and Counseling Services - Mulyani, Mulyani; Suriswo, Suriswo; Sundari, Pristi Aidy; Maulina, Vina; Nihlakn, Mawa; Amali, Tisya Nailin (ASEAN Journal of Empowering Community, 2024)
Children with Special Needs in inclusive schools in Tegal City, especially at the junior high school level, are currently only present in two schools: SMPN 9 and SMPN 5. There are 9 children with special needs at SMPN 9 and 3 children with special needs at SMPN 5, all of whom require assistance in their learning processes. However, in practice, they have not received optimal support due to a lack of specialized human resources in the field. As a result, these students are still provided services similar to those given to normal children, which significantly hinders their learning development in school. Based on the results of the Special Needs Child Assistance activities in Inclusive Schools in Tegal City, especially at SMPN 5 and SMPN 9 Tegal City, there have been changes in social levels, particularly an increase in self-confidence. The learning difficulties experienced have shown improvement, with children starting to complete their tasks well, writing becoming more organized, and being able to speak coherently and manage their emotions. The findings of this activity indicate that special needs children require assistance activities to enhance their development, especially in learning. However, the weakness of this activity is that special needs children in inclusive schools in Tegal City, specifically at SMPN 5 and SMPN 9 Tegal City, still need to be accompanied by special teachers, but in reality, the human resources available in those schools are lacking.